Análise da integridade química da fração fenólica da Justicia acuminatissima (Miq). Bremek (Família Acanthaceae). - Almeida, Hiago Lopes de (Brasil, 2022)
Acanthaceae has approximately 240 genera and 3,250 species distributed throughout tropical and subtropical regions. The genus Justicia acuminatissima stands out, being known as “sara tudo”. Having applied leaves in inflammatory processes. This work aims to analyze the phenolic fraction of J.acuminatissima in gamma radiation with a frequency of 0.5 and 10 kgy, obtaining the mass spectra. The leaves were dried and crushed, submitted to decoction at 60ºC, being alkalized with 25% ammonium hydroxide until pH 10–11, obtaining a basic aqueous phase of the plant leaves (FAqF) separated into two phases, the Aqueous Phase (I ) where it was acidified with HCl to pH 1-2 rich in amino acids, organic acids and sugars, and Organic Phase (II) acidified with HCl to pH 2 rich in flavonoids, aliquots of phenolic fraction FF (10 mg) were coded as FF0, FF5 and FF10 for non-irradiated sample, 5 and 10 KGy. The samples were irradiated in equipment type Panoramic Multipurpose Irradiator Category II, Model/serial number IR-214 and type GB-127, with a dry-stored Cobalt-60 source at maximum activity of 2,200 TBq or 60,000 Ci, the result of the analysis of the chemical integrity of the plant showed that there was a change in the compounds in gamma radiation, and giving the presence of flavonoids in the mass spectra and glucose breakdown fragmentation